(untitled) (Research, Society and Development, 2021)
Introduction: Parkinson’s disease (PD) is a slow and chronic pathology of the nervous system, in which there is a degeneration in the cells of the basal ganglia, causing a loss or interference in the action of dopamine. The aim of this study was to verify the effectiveness of Aquatic Physical Therapy (AF) in balance in patients with Parkinson’s disease through a systematic literature review. Methods: This is a systematic review of the literature, using the electronic databases of Latin American and Caribbean Literature in Health Sciences (LILACS), MEDlars online (MEDLINE), National Library of Medicine and National Institute of Health (PUBMED). ) , Scientific Electronic Library Online (SciELO) and Physiotherapy Evidence Database (PEDro) and had as a search strategy the crossing of these descriptors with the Boolean operators AND and OR. Results and Discussion: The results showed that AF plays a significant role in maintaining balance. Exercises performed on land with the AF to restore balance in patients with Parkinson’s Disease, showed that exercises performed in the aquatic environment were more effective and viable for this type of patient. Final considerations: The AF is a good alternative for optimizing balance, of postural instability and, consequently, to the reduction in the number of falls in elderly patients with PD, with positive repercussions on the QoL of these patients.